Securing the Mobile Future: An Extensive Analysis of the Threat Landscape from Mobile Devices User Perspectives - Aljamal, Mahmoud; Alsarhan, Ayoub; Aljaidi, Mohammad; Mughaid, Ala; Al Jamal, Wafa’ Q.; Twairesh, Abdullah Ewayed (International Journal of Interactive Mobile Technologies (iJIM), 2025)
Mobile devices are becoming increasingly popular in the modern era, posing a significant threat to the security of organizations. As a result, mobile devices have become more and more vulnerable to cyberattacks. The current study aims to assess the threat landscape of mobile devices from the perspectives of users, highlighting the importance of user-centered perspectives in designing solutions to mobile security threats. A total of 47 participants of different demographic profiles were recruited as respondents, and the primary data were collected through an online questionnaire. The study concludes with a discussion of the findings’ implications for research and practice in mobile security. The paper outlines the current state of the art in mobile device security, including vulnerability to security threats, privacy risks, trust in security measures, awareness of potential threats, and satisfaction with the security provided by mobile operating systems. The results demonstrated that users are unaware of data protection and mobile device security, which have a substantial impact on an organization’s performance. However, this study lays a foundational perspective for future advancements in security audits, aiming to enhance cybersecurity practices in an increasingly mobile-centric corporate landscape.